Новые виды рода Philopterus (Mallophaga, Philopteridae) от каменок фауны СССР - Федоренко, И.А. (Вестник зоологии, 1983)
Four species of the genus Philopterus Nitzsch, 1818 are described as new: Ph. oenanthe sp. n. from common wheatear, Ph. pleschankae sp. n. from pied wheatear, Ph. belskayae sp. n. from Finsch's wheatear, ‘and Ph. picatae sp. n. from Eastern pied wheatear. Diagnostic characters of described species and Ph. isabellinae (Mey, 1982) from Isabelline wheatear are given.